A-2=(3+A)

Simple and best practice solution for A-2=(3+A) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for A-2=(3+A) equation:


Simplifying
A + -2 = (3 + A)

Reorder the terms:
-2 + A = (3 + A)

Remove parenthesis around (3 + A)
-2 + A = 3 + A

Add '-1A' to each side of the equation.
-2 + A + -1A = 3 + A + -1A

Combine like terms: A + -1A = 0
-2 + 0 = 3 + A + -1A
-2 = 3 + A + -1A

Combine like terms: A + -1A = 0
-2 = 3 + 0
-2 = 3

Solving
-2 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3x-3+6x-12=180 | | (-3x-7)-(5x+2)= | | 9s-2s=14 | | 4x(x-7)=2x(2x-13)-10 | | 11x+5+10x=180 | | 12(2x-5)=4(6x+1) | | -4x+3-x=18 | | B-1/53.1 | | 6x+4y=4x+4y | | 600+850x=300+1000x | | X/2-4=31/2 | | logx^38=2 | | -2z=-4z-8 | | 4y+9y+5=15 | | x+87+x+111=180 | | n+(n+2)+(n-4)=48 | | 3b-2=4b+4 | | 13.88*5/6 | | -1=64m+(-14m)+9 | | -3+1+6x-4=x+8+5x | | Z^2(a+b)+z^3(a+b)=0 | | r+7=r+7 | | x/8=50 | | 3x-8=x/2 | | 2000=150m+350 | | -(n-8)+2n=-2 | | 38=5+80+-16t^2 | | 8*3x+5=112 | | 0=-4.9t^2+45t+2 | | 6z^2-15z=0 | | 2(x+10)=10 | | 1+2+3+4-6*6= |

Equations solver categories